2015
DOI: 10.1128/jcm.02971-14
|View full text |Cite
|
Sign up to set email alerts
|

Gordonia Species as Emerging Causes of Continuous-Ambulatory-Peritoneal-Dialysis-Related Peritonitis Identified by 16S rRNA and secA1 Gene Sequencing and Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry (MALDI-TOF MS)

Abstract: We report here four cases of continuous ambulatory peritoneal dialysis-related peritonitis caused by three different species of Gordonia. The portal of entry was likely through Tenckhoff catheters. 16S rRNA and secA1 gene sequencing are so far the most reliable methods for the accurate identification of Gordonia species. Gordonia species are Gram-positive weakly acid-fast coryneform bacteria. Although Gordonia species have been implicated in a variety of infections, only seven cases of continuous ambulatory pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 29 publications
1
27
0
1
Order By: Relevance
“…Of the 39 Gordonia species described to date only 10 have been identified as opportunistic pathogens in humans capable to cause a wide range of diseases ranging from primary cutaneous infections or lung infections to bacteremia or recurrent breast abscesses in healthy individuals as well as in immunocompromised patients (Sowani et al 2017 ; Rodríguez-Lozano et al 2016 ). Gordonia is difficult to identify using conventional biochemical tests as reflected in some reports (Tindall and Euzéby 2001 ; Lam et al 2014 ) where all Gordonia isolates were misidentified as Rhodococcus species. To date, sequencing of the 16S rRNA gene has become the most reliable technique for Gordonia species identification (Bizzini et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 39 Gordonia species described to date only 10 have been identified as opportunistic pathogens in humans capable to cause a wide range of diseases ranging from primary cutaneous infections or lung infections to bacteremia or recurrent breast abscesses in healthy individuals as well as in immunocompromised patients (Sowani et al 2017 ; Rodríguez-Lozano et al 2016 ). Gordonia is difficult to identify using conventional biochemical tests as reflected in some reports (Tindall and Euzéby 2001 ; Lam et al 2014 ) where all Gordonia isolates were misidentified as Rhodococcus species. To date, sequencing of the 16S rRNA gene has become the most reliable technique for Gordonia species identification (Bizzini et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MALDI-TOF MS based system has emerged as new tool with the possibility to identify most of the microorganisms causing human infections (Lam et al 2014 ). Different studies evaluated the precision of MALDI-TOF MS for Gordonia species identification with not very promising results (Hsueh et al 2014 ; Rodríguez-Lozano et al 2016 ; Barberis et al 2014 ; Bizzini et al 2010 ; Lai et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…as other gram-positive bacilli, such as Rhodococcus or Nocardia spp. However, so far bacterial rRNA gene sequencing analysis has proven to be a more accurate measurement [10]. As Lai CC et al reported, in a group of 66 isolates previously identified as Rhodococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…They are sometimes dismissed as Corynebacteria , Nocardia , or Rhodococcus species [12, 13, 16, 17]. It is also believed that the incidence of Gordonia infections has been underestimated.…”
Section: Discussionmentioning
confidence: 99%